Case Study of Cancer Patients Treated with Herbal Acupuncture Therapy - Hwa-Seung Yoo; Jung-Hyo Cho; Yeon-Weol Lee; Chang-Gue Son; Chong-Kwan Cho (Korean Pharmacopuncture Institute, 2004)
Objective : This study was aimed to validate the Herbal Acupuncture Therapies(HAT) for cancer patients. Patients and methods : This retrospective study was performed on 8 patients who were diagnosed as cancer in Korea and treated with HAT in the oriental hospital of Daejeon University, from January 2003 to January 2004. We retrospectively analyzed the medical records of 8 patients for improvement of symptoms, toxic effects of liver and kidney, myelosupression and changes of Quality of Life(QOL). Results : Analysis of change of chief complaints showed that 75% patients replied moderate relief and 25% replied complete relief in Likert scale. Analysis of Liver Function Test(LFT), Renal Function Test(RFT) level showed that HAT does not have toxic effects on liver and kidney. Analysis of Complete Blood Count(CBC) level showed that HAT does not have myelosuppression effects on bone marrow. Analysis of QOL showed that 100% patients replied improvement in Eastern Cooperative Oncology Group status(ECOG) status. Conclusion : Our findings suggest that HAT offer potential benefits for cancer patients.